2019
DOI: 10.1002/jat.3926
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of vanadium oxide nanoparticles and titanium dioxide‐coated vanadium oxide nanoparticles to human lung cells

Abstract: Due to excellent metal-insulator transition property, vanadium dioxide nanoparticles (VO 2 NPs)-based nanomaterials are extensively studied and applied in various fields, and thus draw safety concerns of VO 2 NPs exposure through various routes. Herein, the cytotoxicity of VO 2 NPs (N-VO 2 ) and titanium dioxide-coated VO 2 NPs (T-VO 2 ) to typical human lung cell lines (A549 and BEAS-2B) was studied by using a series of biological assays. It was found that both VO 2 NPs induced a dose-dependent cytotoxicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
0
27
0
2
Order By: Relevance
“…demonstrated that some synthetic V complexes showed pro-apoptotic activities in MGC803 (human gastric cancer cell line) cells related to the increase in proteins such as Bax, caspases 3 and 9, as well as the decrease in Bcl2 [31]. On the other hand, Xi et al reported the induction of apoptotic cell death in A549 and BEAS-2B lung cancer lines associated with the overexpression of caspase 3 induced by the exposure to V nanoparticles [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that some synthetic V complexes showed pro-apoptotic activities in MGC803 (human gastric cancer cell line) cells related to the increase in proteins such as Bax, caspases 3 and 9, as well as the decrease in Bcl2 [31]. On the other hand, Xi et al reported the induction of apoptotic cell death in A549 and BEAS-2B lung cancer lines associated with the overexpression of caspase 3 induced by the exposure to V nanoparticles [32].…”
Section: Discussionmentioning
confidence: 99%
“…Vanadium has been reported as a possible chemotherapeutic agent for different types of neoplasms. Some antineoplastic drugs have been administered by aerosol delivery with promising results [20,32]. Here, we propose V as a potential antineoplastic agent for lung cancer by aerosol delivery that will reduce the number of tumor cells and possibly the systemic side effects reported for V. Other V compounds need further analysis to find the dose and the best protocol for the administration for this element, which opens another possible treatment for NSCLC.…”
Section: Aerosol Deliverymentioning
confidence: 99%
“…[ 47–49 ] BEAS‐2B cells were observed to undergo squamous differentiation in the presence of 2% FBS, spurring the development of serum‐free culture media such as LHC‐9 and BEGM. [ 21 ] Even so, many reports utilize RPMI [ 31,50–52 ] or DMEM [ 32,41,53,54 ] with up to 10% FBS. These FBS concentrations raise concerns about squamous differentiation in BEAS‐2B cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20,21 ] Even so, many studies with BEAS‐2B cells and nanotoxicity utilize over 2% serum in the cell culture medium, potentially causing conflicting results ( Figure 1 ). [ 22–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…BNPs, after 24 h exposure, induced 100% of Daphnia magna mortality for concentrations above 80 mg/L [ 13 ]. For VNPs, reactive oxygen species (ROS) generation, mitochondrial damage and apoptosis were observed in human lung cells [ 14 , 15 ]. Wörle-Knirsch et al (2007) [ 16 ] also reported cell viability reduction and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%